ANALISIS PENGARUH LATAR BELAKANG PENDIDIKAN, PELATIHAN DAN PENGEMBANGAN, SUPERVISI AKADEMIK TERHADAP KOMPETENSI PROFESIONAL GURU AKUNTANSI PADA SEKOLAH MENENGAH KEJURUAN DI KABUPATEN LANGKAT DENGAN MOTIVASI SEBAGAI VARIABEL MODERATING - Trysanti Kisria Darsih (Jurnal Sintaksis, 2019)
The objective of the research was to analyze the influenced of education background,training and development, and academic supervision on the professional competence of Accounting teachers at the SMK (Vocational Schools) in Langkat Regency with motivation as moderating variable. The research used causal associative method. The population was 45 SMK Accounting teachers in Langkat Regency as the respondents, and all of them were used as the samples (total sampling). Primary data were gathered by distributing questionnaire to the respondents and analyzed by using multiple regression analysis and residual test. The result of the research showed that educational background, training and development, and academic supervision simultaneously had positive and significant influence on professional competence of SMK Accounting teachers in Langkat Regency. Partially, educational background, training, and development had positive and significant influence on professional competence of SMK Accounting teachers in Langkat Regency, while academic supervision did not have any significant influence on SMK Accounting teachers in Langkat Regency. Motivation was not able to moderate the correlation of educational background, training and development, and academic supervision with professional competence of SMK Accounting teachers in Langkat Regency.